Hubungan Tingkat Pengetahuan Ibu dengan Pemberian ASI-Eksklusif di Desa Tamansare Kecamatan Dungkek Kabupaten sumenep - Hosnu Inayati; Sri Sumarni; zakiyah Yasin; Nita Dwi Jayanti (Wiraraja Medika : Jurnal Kesehatan, 2019)
ABSTRACT Exclusive breastfeeding for infants aged 0-6 months who are given only breast milk, without complementary food and other beverages. The intended complementary foods for breast milk are honey, water, formula milk, tea water, or solid food such as papaya, rice porridge, team, banana biscuit. The purpose of this study was to determine the level of knowledge of breastfeeding mothers with exclusive breastfeeding in Tamansare Village, Dungkek District, Sumenep Regency. This type of research is quantitative analysis with the Cros Sectional approach.The population in this study were all mothers breastfeeding infants aged 0-6 months as many as 30 people and The sample size in this study is that some breastfeeding mothers in infants aged 0-6 months were 30 people, with total sampling technique.The research instrument used in this study is the questionnaire,then spread to mothers who have babies aged 0-6 months,the data obtained in the study were processed using the chi square test with a significance level of 0,05. Based on the results of the research obtained for maternal knowledge, it was found that most mothers had sufficient knowledge, namely 22 (73.4%),Exclusive breastfeeding was obtained by almost all mothers not giving exclusive breastfeeding as many as 29 (96.7%).And there is a significant relationship between the knowledge of mothers with exclusive breastfeeding, namely p = 0,033. The effort to increase the coverage of exclusive breastfeeding is to provide more intensive education and health promotion about exclusive breastfeeding should be applied so that the level of knowledge of mothers about breastfeeding is better than in previous years and aims to change people's habits in providing complementary feeding or formula milk and food / drink until the baby is 6 months old. Keywords :Mothers Knowledge, Giving Exclussiv ASI